Moral Property Rights in Bargaining with Infeasible Claims - Simon Gächter; Arno Riedl (Tinbergen Institute, 2003)
In many business transactions, in labor-management relations, in internationalconflicts, and welfare state reforms bargainers hold strong entitlements that are oftengenerated by claims that are not feasible any more. These entitlements seem to considerablyshape negotiation behavior. By using the novel setup of a 'bargaining with claims' experimentwe provide new systematic evidence tracking the influence of entitlements and obligationsthrough the whole bargaining process. We find strong entitlement effects that shape openingoffers, bargaining duration, concessions and reached (dis-)agreements. We argue thatentitlements constitute a 'moral property right' that is influential independent ofnegotiators' legal property rights.
Keywords: A12; D63; C78; C92; 330; Moral property rights; fairness judgments; bargaining with claims; self-serving bias; Verhandlungstheorie; Eigentumsrechtstheorie; Test; Theorie; Soziale Beziehungen